Kesejahteraan Sumber Daya Manusia Distributor Unilever Pada CV. Ambasador Zulias Kabupaten Sengkang - Didin Wahyudi; Sabri Sabri (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
The welfare program provided by the company to employees should be beneficial for both the company and the employees, so that it can encourage the achievement of effective company goals. Employee welfare programs should be in accordance with the provisions set by the company and do not violate government regulations. The main objective of this study was to determine the level of Welfare of Unilever Distributor Human Resources at CV Ambassador Zulias, Sengkang Regency. This study uses qualitative research methods, with data collection techniques through interviews, observation, and document review. The results of this study indicate that the Welfare of Unilever Distributor Human Resources at CV Ambasador Zulias Sengkang Regency is classified as good in terms of economic welfare, facility welfare and service welfare. However, there are some things that need to be improved, such as the provision of official clothing for employees and facilities for worship in the office. Welfare of employees at CV Ambasador Zulias Sengkan Regency has been assessed as good in terms of income standards that come from various sources such as pensions, salaries, holiday allowances, bonuses whose aim is for the welfare of its employees